Jesus and the marginalized: attaching pastoral meaning to Luke 4:14-30 - J. Steyn; A. Yousaf (Acta Theologica)
In Luke 4:14-30, Jesus revealed Himself in fulfilling the prophecy of Elijah and Elisha and being the Saviour of the marginalized. The calling of the pastoral caregiver is to be the hands and feet of Jesus, especially to the marginalized. Jesus also brought reconciliation and spiritual transformation to the person in need. Luke portrays Jesus as the anointed one through the Spirit. Three keys provide access to the understanding of the passages in Luke, of which the first is exegeses of the passages themselves and in historical context. Secondly, interactive internalization provides the reader of the passages with the opportunity to focus on the Word and Spirit and to internalize the event. Thirdly, through the process of appropriation, spiritual growth and transformation takes place.